KOMUNIKASI INTERPERSONAL KEPALA DESA SAKERTA TIMUR KECAMATAN DARMA KABUPATEN KUNINGAN DALAM MEMBINA GENERASI MUDA - Rifqi Fauzi (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2021)
The objectives of this study are: 1) to determine the interpersonal communication model of the village head in fostering the younger generation, 2) to find out the forms of interpersonal communication of the village head in fostering the younger generation, 3) to determine the effect of interpersonal communication on the village head of Sakerta Timur District Darma Kuningan Regency in fostering the younger generation. This research uses a qualitative method with a case study approach. Data collection techniques used include: observation, in-depth interviews, and documentation studies. The data analysis technique used in this research is a qualitative descriptive analysis technique. Meanwhile, the validity of the data was checked using the source triangulation technique. The results of this study indicate that: 1) The interpersonal communication model of the Village Head in fostering the younger generation by using a linear model, an interactive model and a transactional model of the three models is used in interacting between the Village Head and youth in East Sakerta in formal and non-formal activities. 2) The form of interpersonal communication of the Village Head in fostering the younger generation, does not escape the form of interpersonal communication that is often used daily by youth, including the first form of interpersonal communication through conversation, dialogue and sharing. 3) The effect of the Village Head's interpersonal communication in fostering the younger generation is to express concern for others, find oneself, discover the outside world, build and maintain harmonious relationships, and influence attitudes and behavior.